Review: The Bible in the Renaissance. Essays on Biblical Commentary and Translation in the Fifteenth and Sixteenth Centuries - Brooks, Peter Newman (The journal of theological studies, 2003)
The Bible in the Renaissance. Essays on Biblical Commentary and Translation in the Fifteenth and Sixteenth Centuries Richard Griffiths xviii + 204 Aldershot, UK/Burlington, VT/Singapore/Sydney (St Andrews Studies in Reformation History.). Ashgate 2001 £47.50 0 7546 0394 6